Postnatal Development of the Retina in Rats Exposed to Hyperoxia: A Fractal Analysis. (15th April 2013) - Ştefănuţ, Anne Claudia; Ţălu, Ştefan; Miclăuş, Viorel; Mureşan, Adriana; Moldovan, Remus; Szabo, Bianca
Abstract : Purpose . The aim of this study was to investigate and quantify changes in the newborn rats retinal layers during the hyperoxia (80% O2 ) exposure using fractal analysis. Materials and Methods . This study was conducted on two groups of 20 newborn rats: a control (normal) group (10 rats) and an experimental group (10 rats). The control group was composed of 10 newborn rats, which were placed at 12 hours after birth, in a pediatric incubator, together with their mother, in conditions of normoxia for 21 days. The experimental group consisted of 10 newborn rats, which were placed at 12 hours after birth, in a pediatric incubator with their mother, in conditions of normoxia for 7 days, then 7 days of hyperoxia (80% O2 ) for 22.5 hours/day, and then 7 days in conditions of normoxia. Slaughtering of the rats was performed on day 21 and the eye globes were harvested in order to perform histopathological examinations. The fractal analyses of the retinal digital images were performed using the fractal analysis software Image J, and the fractal dimensions were calculated using the standard box-counting method. Results . Microscopic examination revealed a normal development of the retina in the control group. In the experimental group, all the animals exposed to hyperoxia revealed both structural and vascular abnormalities on entire retina. Conclusions . The results showed that the fractal analysis is a valuable tool to quantify histoarchitectural changes in the newborn rats retinal layers during the hyperoxia (80% O2 ).